DESIGNING AND IMPLEMENTATION OF A SECURITY SYSTEM VIA UML: SMART DOORS - Jasim, Yaser A.; Alsaaigh, Mustafa O.; Saeed, Mustafa G. (CSRID (Computer Science Research and Its Development Journal), 2020)
Companies or estate have problems stealing employees of items or records by using common keys because the usual key is less reliable. This paper seeks to control intelligent doors by means of a RFID card. In addition, a security system was created for employee entrances and exits with a system-specific server and may allow staff to open a particular door and specify a time for RFID card operation. The design and implementation of a robust and intelligent system were thus designed to control an employee's or a person's entry and exit through the use of an intelligent key and smart doors. This paper proposes the safety improvement plan based on the Smart Door Lock System for the security problem caused by the physical key in unmanned automation machines, like ATMs, KIOSKs and sales machines. The use of hardware and software inventions to construct this program was an effective factor.